1967
DOI: 10.1021/ja01000a086
|View full text |Cite
|
Sign up to set email alerts
|

Exo-endo relative reactivities in three representative U-shaped systems. Exo-endo rate ratio in solvolysis as a steric phenomenon

Abstract: Solvolysis as a Steric PhenomenonSir : We wish to report that in three representative Ushaped systems examined, cis-bicyclo[3.3.0]octane, norbornane, and endo-5,6-trimethylenenorbornane, noncarbonium ion reactions exhibit preferences for reaction at the exo face that are comparable in magnitude to the exo:endo rate ratios observed in the solvolyses of the tertiary methyl p-nitrobenzoates. This common pattern of reactivity suggests that steric factors must contribute to the greater reactivity from the exo dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1970
1970
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…The structural assignment to adducts 11a-c was unequivocally established by 1 H-NMR spectroscopy, since the absence of vicinal coupling constants between protons H-1 and H-2 as well as between protons H-3 and H-4 (Scheme 1) is a clear indication of their exo configuration. 49,50 By taking into account the outcome of reactions carried out on olefins structurally related to 8, 51,52 we assigned the exo configuration even to spirocyclic intermediates 9a-c, which were the only isomers isolated in each cycloaddition step. Finally, the pericyclic reaction of pyridinenitrile oxides with olefin 12 yielded bicyclic cycloadducts 13a-c.…”
Section: Resultsmentioning
confidence: 99%
“…The structural assignment to adducts 11a-c was unequivocally established by 1 H-NMR spectroscopy, since the absence of vicinal coupling constants between protons H-1 and H-2 as well as between protons H-3 and H-4 (Scheme 1) is a clear indication of their exo configuration. 49,50 By taking into account the outcome of reactions carried out on olefins structurally related to 8, 51,52 we assigned the exo configuration even to spirocyclic intermediates 9a-c, which were the only isomers isolated in each cycloaddition step. Finally, the pericyclic reaction of pyridinenitrile oxides with olefin 12 yielded bicyclic cycloadducts 13a-c.…”
Section: Resultsmentioning
confidence: 99%
“…122 ± 125 Earlier, the configuration of the epoxides has been studied by converting them into known norbornanols; thus, it was found that the epoxynorbornane formed contains only a slight amount of the endo-epoxide (6%, 126 0.5% 127 ). Brown et al 127 attributed the exo-attack to the predominant steric hindrance of the endo-area by the norbornene fragment. As model compounds, they chose norbornene (1), cisbicyclo[3.3.0]octene, and endo-5,6-trimethylenonorbornene 10.…”
Section: Stereochemistry Of Epoxidation Of Substituted Norbornenes Wi...mentioning
confidence: 99%
“…The increase in the steric hindrance of the endo-area of the ring was judged by the increase in the exo-stereoselectivity. 127 Later, the selectivity of the attack and the high reactivity of norbornene have been explained by the influence of hyperconjugation and out-of-plane deformation. Theoretical studies showed that the =C±H bonds in norbornene, unlike those in cyclohexene or bicyclo[2.2.2]octene, are bent by 2 ± 5 8 to the endo-area.…”
Section: Stereochemistry Of Epoxidation Of Substituted Norbornenes Wi...mentioning
confidence: 99%
“…(9) T. T. Tidwell, ibid., 92, 1448Tidwell, ibid., 92, (1970. < 10) H. C. Brown andJ. H. Kawakami, ibid., 92, 1990 (1970).…”
mentioning
confidence: 99%
“…Epoxidation-Reduction of Norbornene. The epoxidation of 0.94 g (10 mmol) of norbornene with 2.20 g (10 mmol) of 78% m-chloroperbenzoic acid was complete within 20 min, but stirred at room temperature for 1 hr. Reduction with lithium-ethylenediamine and analysis on UCON LB 550X at 100°indicated 99.0% exonorbornanol, 0.3% endo-norbornanol, 0.5% nortricyclanol, and 0.2% 7-norbornanol in 87% yield in order of increasing retention time.…”
mentioning
confidence: 99%